The psychology of countering terrorism with technology. - Stout, C.E.
This article takes a sober approach to what individuals can do to be better prepared to deal with the uncertainty of these times vis-a-vis the terrorist pall and offers realistic considerations of how the complex mechanisms of terrorism may play out, without alarmist hyperbole, and approaches of situation assessment, appropriate content provision, and concomitant information dissemination. Accurate risk assessment when combined with appropriate preparation can go a long way in mitigating unwarranted fears and anxieties, as well as provide a more rational and appropriate use of the technological tools that are (and will be) available.
Keywords: Complex mechanisms; Concomitant information dissemination; Content provision; Psychology; Situation assessment; Technological tools; Terrorism; Terrorist pall; Unwarranted anxieties; Unwarranted fears